2001
DOI: 10.1161/01.str.32.8.1920
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Choice of Halothane Versus Propofol

Abstract: Background and Purpose-It is not known whether preischemic exposure to anesthetic agents affects the amount of damage from transient focal ischemia that occurs after cessation of the anesthetic. We compared the effect of prior exposure to halothane or propofol on infarction size after transient middle cerebral artery occlusion (MCAO) induced in the awakening animal to test the hypothesis that anesthetic type and exposure duration would independently affect the amount of brain injury. Methods-Male Wistar rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 35 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Because most anesthetics are neuroprotective when present during ischemia (Miura et al, 1998;Bhardwaj et al, 2001), we awakened rats immediately once the arterial occlusion was achieved to minimize the presence of anesthetics during ischemia and to maximally simulate clinical situation. Similar to the results reported before (Kapinya et al, 2002;Xiong et al, 2003), isoflurane preconditioning improved neurological outcome assessed within 4 days after the MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…Because most anesthetics are neuroprotective when present during ischemia (Miura et al, 1998;Bhardwaj et al, 2001), we awakened rats immediately once the arterial occlusion was achieved to minimize the presence of anesthetics during ischemia and to maximally simulate clinical situation. Similar to the results reported before (Kapinya et al, 2002;Xiong et al, 2003), isoflurane preconditioning improved neurological outcome assessed within 4 days after the MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…Kapinya et al (2002a) observed that in male rats, a 3 h pretreatment with 1.2% (1 MAC) halothane 24 h before permanent MCAO reduced infarct volume measured 4 days after initiation of ischemic injury. In a transient model of focal ischemia in male rats comparing the effects of immediate preischemic exposure of halothane and propofol, a 1 h exposure of 1% to 2% halothane attenuated infarction volume compared with propofol (10 mg/kg bolus, 30 mg/kg per hour infusion) whereas no differences in infarct size were seen between halothane and propofol treatment groups when the preischemic exposure period was extended to 8 h (Bhardwaj et al, 2001). Even fewer in vitro studies have been performed examining halothane preconditioning effects on neuronal injury.…”
Section: Halothanementioning
confidence: 97%
“…[1][2][3][4][5] In a model of incomplete hemispheric ischemia, Baughman et al 1 demonstrated neuroprotection in rats anesthetized with isoflurane or halothane. Warner et al 2 demonstrated the neuroprotective effect of halothane or sevoflurane during focal cerebral ischemia in rats.…”
mentioning
confidence: 99%
“…3 Miura et al 4 provided evidence that protection against neuronal injury by isoflurane during near-complete ischemia is superior to protective effects of fentanyl or ketamine anesthesia. In a recent publication, Bhardwaj et al 5 presented data on neuroprotection with halothane anesthesia after focal cerebral ischemia induced immediately after the termination of anesthesia. All these studies used volatile anesthetics shortly before and during the ischemic period.…”
mentioning
confidence: 99%